MENGKAJI FEMINISME DALAM NASKAH DRAMA MONOLOG DONGENG MARSINAH KARYA SAPARDI DJOKO DAMONO - Intan Rosmawati (BADAN PENERBIT STIEPARI PRESS, 2022)
This article discusses the script for the monologue drama Dongeng Marsinah by Sapardi Djoko Damono. The background of this discussion is to (1) explain the drama script and feminism in the Marsinah fairy tale and (2) examine feminism in the Marsinah fairy tale. The method used in this research is descriptive analytic with the collection in the form of a literature study. The primary data source is obtained from the monologue drama script Marsinah Fairy Tale by Sapardi Djoko Damono, and is equipped with secondary data sources from books, scientific journals, articles and the internet. The results show that this drama script is based on the transformation of poetry which is carried out in a monologue and the Marsinah fairy tale contains a feminism movement, where feminism is a movement and awareness that departs from the assumption that women are basically oppressed and exploited, as well as efforts to be established and exploited. Feminism theory is the original picture of patriarchal social reality. Starting from the turmoil of women who are oppressed by the patriarchal social system. The first character Marsinah is described as a victim of the patriarchy and the patriarchal is a teacher who is assisted by the government in oppressing the main character, Marsinah. The two impacts of the patriarchy have a bad influence on the main character so that Marsinah's life is lost.